An Action Research on Teaching Science through Technology Supported Inquiry - based Learning: A Pilot Study. (13th May 2015) - Unlu, Zeynep Koyunlu; Dokme, Ilbilge; Tufekci, Aysel
Abstract: The developed and developing countries are making an effort to enhance the quality of science education. Investments and research in this area are constantly increasing. The aim of this action research in which the teacher and the researcher were the same person to make the science education more effective. The research was planned in two cycles. The first cycle consisted of identifying the problems, developing and implementing the action plan, gathering and analyzing the data, and evaluation. The participants of this first cycle were 6 students and a teacher. The first cycle that was also planned as the pilot study lasted about three months in the 2013-2014 school year. The study started with an identification of the existing problems. In order to address the problems encountered in the field, an action plan, including technology supported inquiry based learning, was developed and implemented. To evaluate the effectiveness of the implementation, quantitative (achievement tests) and qualitative (interviews, observations and documents) data were collected and analyzed. The results revealed that the first cycle of this action research will be used in developing an action plan for the second cycle to be implemented in the 2014-2015 school year.